Spatiotemporal propagation dynamics of intense optical pulses in loosely confined gas-filled hollow-core fibers - 赵睿睿 王丁 黄志远 冷雨欣 李儒新 (中国物理B：英文版, 2017)
We numerically study the propagation dynamics of intense optical pulses in gas-filled hollow-core fibers(HCFs). The spatiotemporal dynamics of the pulses show a transition from tightly confined to loosely confined characteristics as the fiber core is increased, which manifests as a deterioration in the spatiotemporal uniformity of the beam. It is found that using the gas pressure gradient does not enhance the beam quality in large-core HCFs, while inducing a positive chirp in the pulse to lower the peak power can improve the beam quality. This indicates that the self-focusing effect in the HCFs is the main driving force for the propagation dynamics. It also suggests that pulses at longer wavelengths are more suitable for HCFs with large cores because of the lower critical power of self-focusing, which is justified by the numerical simulations. These results will benefit the generation of energetic few-cycle pulses in large-core HCFs.